Kekerasan dalam Rumah Tangga: Perspektif Psikologis dan Edukatif - Wahab, Rochmat (Unisia, 2010)
Every family hopes to build harmony family, happy family, and mutual loving each others. Infact, there are several violences that happen in family life either physically, psychologically, sexually, or emotionally. The violence in family because of intemal and extemal factors either individually or collectively. In particular in the age of information nowadays the violence cultures emerges by information that producing by media, both printed media and electronic media, the condition tends to influence the development of children, so that they can not grow naturally, they can not reach high score in their school. Hence, it needs to be conducted psychologically, educatively, preventively, and curatively toward the cases that happen in family life, especially the victims and society in general.